A bibliometric analysis on gift giving. Issue 4 (28th December 2022) - Gupta, Mansi; Parvathy,; Givi, Julian; Dey, Moumita; Kent Baker, H.; Das, Gopal
Abstract: Gift‐giving is a typical consumer behavior with important implications for consumers and marketers. Accordingly, consumer gift‐giving behavior has received much attention from marketing scholars. We conduct a bibliometric analysis of 237 articles on gift‐giving from the Web of Science database. This analysis identifies the bibliometric attributes of the gift‐giving literature, including its publication trend, influential outlets, impactful articles, prolific scholars, international scope, state of collaboration, and featured topics and themes. Using content analysis, we identify three themes that categorize the consumer gift‐giving literature's key segments: (1) broad and nuanced outlooks of the social side of gift‐giving, (2) the less pleasant side of gift‐giving, and (3) the foundational research on consumer gift‐giving. This paper provides readers with a state‐of‐the‐art overview of consumer gift‐giving literature and identifies opportunities for future gift‐giving research.